Back to the roots in football science. Why it might be smart to invest in the youngest players talent - Faude, O. (Science and Medicine in Football, 2018)
Currently, the world is looking to Russia, where 736 players are striving for becoming world champions in football (soccer). This event dominates the reporting in mass media and is associated with considerable economic interests. In addition, an enormous amount of children is watching the games, thereby admiring their favorite players and desiring to become one of the next generation heroes. Professionals make up clearly less than 1% of organized football players worldwide. Children are the largest part of the active football family. The FIFA Big Count from 2006 showed that 56% of all registered football players worldwide were youth athletes (FIFA 2007). It seems very unlikely that the numbers relevantly changed during the last decade. In Germany, for instance, recent data show that nearly 62,500 adult teams are opposed by about 95,000 youth teams, of which more than three quarters are under-15 teams (DFB 2017). Less than 1500 athletes are playing in one of the three highest national divisions in Germany. This unequal distribution is nearly inverted by the scientific efforts, which are invested in the different populations. For instance, from the papers published in "Science and Medicine in Football" since launched as an independent journal (January 2017 until 21 June 2018), 72% reported data from elite level athletes (adult or junior), 16% focused on semi-professionals and amateur adult players, and 7% on specific groups or methods (referees, goalkeepers, recreational players, coaching, biomechanical modeling). Only 5 articles (5%) referred to children of a lower playing level. Reasons for this discrepancy might be seen in the great attention, which is associated with elite football. When working with professional players, it is very likely that this research will also attract interest in the scientists behind it. The opportunity for junior academics to become employed in professional football might be another attractive rationale. Furthermore, there is a lot of money in the professional football business, increasing the chance that elite football research is better funded. Research in football kids, however, has several limitations and disadvantages: Possibly, study results might generate a lower scientific impact; there is likely less money available from funding institutions to do research in football kids; and the attention from media and society is clearly lower compared to professional football. Consequently, research in children may appear less attractive. Next to these limitations, there are some advantages: Football kids are a large population, available all around the world. Thus, we can do large, statistically powerful, and methodologically strong scientific studies, potentially generating a high scientific impact. The scientific knowledge in children ´s football is currently scarce. For instance, we know very little about the development of pre-pubertal kids from their start in football up to the adult (elite) level, particularly regarding prospectively followed interactions of training and biological maturation. We need to know more about the long-term development of young players, particularly from a health (not necessarily a performance) perspective. As previous injury is likely a main risk factor for future injuries (Emery 2003), it is interesting whether injury prevention starting at an early age (Rossler et al.2018) is an appropriate means to prevent injuries in later stages of athletic development. There is evidence that talent identification is not reliably possible until puberty is finished (Güllich 2014; Höner et al.2017)and that early specialization might beharmful for talent development (Sugimoto et al.2017). Many football academies start their talent development programs at very young ages, often in prepubertal children, and researchers jump on the bandwagon. It is questionable, however, whether it is promising to invest into a relatively small number of possibly talented, but very young players. It might be more appropriate to study the huge crowd of active players, irrespective of their actual performance level (going out of the academies to the grass roots), establishing scientific evidence from large, methodologically strong studies on the ideal development of football kids through their early stages as active players (from a physiological, motor skill, psychosocial, and health perspective). In these age categories, children are often coached by not or poorly trained people for 2-3 h per week (except for the few who reached the academies). Research in the youngest players may allow (i) for establishing general guidelines for these untrained coaches in order to support an appropriate development in as many kids as possible,(ii) for supporting an active and healthy way into lifelong physical activity, and (iii) for providing the broadest possible basis for talent development in post-pubertal stages, i.e., at a time when talent identification and development becomes more reliable and, thus, promising. It seems auspicious to develop an evidence-based adaptation of the long term athletic development model (Lloyd and Oliver 2012), particularly tailored to football. In conclusion, there are convincing reasons suggesting that (scientifically) investing in the bulk of kids who are glancing at the TVs with great dreams this summer may be an appropriate way to improve the level of professional play in future, on the one hand side, and to develop healthy and active kids, on the other hand side. It is time to carefully shift the focus of research from the elite level to the roots of football.